Discourse analysis of the story of Sheikh Sanan from the book Mantiq al-Tayr by Attar Neyshaburi based on the Van Leeuwen model - Faezeh Arab Yousefabadi; Saeid Ghafrooi (ادبیات عرفانی)
Mantiq al-Tayr is a mystical work in which the story of Sheikh Sanan occupies a special place due to the use of social agents and different ways of representing social agents. The aim of this research is to analyze the discourse of the story of "Sheikh Sanan" based on the Van Leeuwen model. This research was conducted using a mixed qualitative and quantitative method and examined the way social agents are represented in the text through structural and linguistic analysis. The results of this research show that Sheikh Sanan is introduced in this story through the activation of a dynamic and influential force that at the end of the story manages to overcome the obstacles to his spiritual advancement and connects an opposing force such as the infidel girl from the opposing group with his own group. In this story, the highest frequency of titles is reserved for Sheikh Sanan, and after that, the highest frequency of titles refers to the infidel girl, who, due to her final inclination towards the Sheikh, has had a tremendous impact on the image and spiritual legitimacy of the Attar order. In the story, the highest frequency of links is related to the path-centered group, which represents Attar's mystical ideology. In the obscuring section, it was revealed that in this story, the anonymous agents who propagate the path-oriented discourse are marginalized in terms of identity and the action they perform to serve the mystical discourse is emphasized; also, in the deletion component, it was proven that in addition to the parts that were completely deleted from the narrative, the use of verbs with unknown subjects through diminution is in line with strengthening the spiritual aspects of the text.